2022
DOI: 10.34133/2022/9847962
|View full text |Cite
|
Sign up to set email alerts
|

Deep UV Microscopy Identifies Prostatic Basal Cells: An Important Biomarker for Prostate Cancer Diagnostics

Abstract: Objective and Impact Statement. Identifying benign mimics of prostatic adenocarcinoma remains a significant diagnostic challenge. In this work, we developed an approach based on label-free, high-resolution molecular imaging with multispectral deep ultraviolet (UV) microscopy which identifies important prostate tissue components, including basal cells. This work has significant implications towards improving the pathologic assessment and diagnosis of prostate cancer. Introduction. One of the most important indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…c Blind inference of a trained virtual staining model. The virtual histology images are rapidly generated from label-free images using a digital computer smears 39 , as well as H&E 40 and IHC 41 staining on prostate tissue sections; photoacoustic microscopy was also demonstrated to achieve virtual H&E staining of mouse brain 42 and frozen sections of bone tissue 43 . As another example, Mayerich.…”
Section: Label-free Virtual Stainingmentioning
confidence: 99%
“…c Blind inference of a trained virtual staining model. The virtual histology images are rapidly generated from label-free images using a digital computer smears 39 , as well as H&E 40 and IHC 41 staining on prostate tissue sections; photoacoustic microscopy was also demonstrated to achieve virtual H&E staining of mouse brain 42 and frozen sections of bone tissue 43 . As another example, Mayerich.…”
Section: Label-free Virtual Stainingmentioning
confidence: 99%
“…Recently, it has been demonstrated for fast hematology analysis of whole blood smears and blood samples in custom microfluidic cartridges for point-of-care applications enabled by advancements in low-cost UV LEDs and sensors [9][10][11][12][13]. UV microscopy has also been used for multi-spectral, label-free histopathology of tissue samples [14][15][16]. In these prior works, deep neural networks have been required to pseudo-colorize images to mimic conventional biochemical stains (i.e., hematoxylin and eosin, Giemsa) [12,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies demonstrated UV microscopy for biomolecular mass-mapping in live cells without observable photodamage [7,9,10]. Recently applications of UV microscopy have included hematology analysis of whole blood samples and label-free histopathology of prostate cancer sections and fresh brain tissue [11][12][13][14][15][16][17]. In addition, live single-cell imaging with UV microscopy has been demonstrated for analysis of intracellular dynamics in cancer cells and T-cell phenotyping [18].…”
Section: Introductionmentioning
confidence: 99%